Variability of Gut Microbiota Across the Life Cycle of Grapholita molesta (Lepidoptera: Tortricidae) - Wang, Xueli; Sun, Shengjie; Yang, Xuelin; Cheng, Jie; Wei, Hongshuang; Li, Zhen; Michaud, J. P.; Liu, Xiaoxia (Frontiers in Microbiology, 2020)
Grapholita molesta, the oriental fruit moth, is a serious global pest of many Rosaceae fruit trees. Gut microorganisms play important roles in host nutrition, digestion, detoxification, and resistance to pathogens. However, there are few studies on the microbiota of G. molesta, particularly during metamorphosis. Here, the diversity of gut microbiota across the holometabolous life cycle of G. molesta was investigated comprehensively by Illumina high-throughput sequencing technology. The results showed that the microbiota associated with eggs had a high number of OTUs. OTU and species richness in early instar larvae (1st and 2nd instar) were significantly higher than those in late instar larvae (3rd-5th instar). Species richness increased again in male pupae and adults, apparently during the process of metamorphosis, compared to late instar larvae. Proteobacteria and Firmicutes were the dominant phyla in the gut and underwent notable changes during metamorphosis. At the genus level, gut microbial community shifts from Gluconobacter and Pantoea in early instar larvae to Enterococcus and Enterobacter in late instar larvae, and to Serratia in pupae were apparent, in concert with host developmental changes. PCoA and LEfSe analyses confirmed the differences in the structure of gut microbiota across different developmental stages. In addition, sex-dependent bacterial community differences were observed. Microbial interaction network analysis showed different correlations among intestinal microbes at each developmental stage of G. molesta, which may result from the different abundance and diversity of gut microbiota at different life stages. PICRUSt analysis indicated that most functional prediction categories of gut microbiota were related to membrane transport, carbohydrate and amino acid metabolism, DNA replication and repair. Bacteria isolated by conventional culture-dependent methods belonged to Proteobacteria, Firmicutes and Actinobacteria, which was consistent with high-throughput sequencing results. In conclusion, exploration of gut bacterial community composition in the gut of G. molesta should shed light into deeper understanding about the intricate associations between microbiota and host, and might provide clues to the development of novel pest-management strategies against fruit borers.